2005
DOI: 10.1590/s1516-89132005000300011
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological analysis of critical points in the chicken industry

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
2
2
0
1
Order By: Relevance
“…Moreover, our results showed that chicken had the highest level of contamination, while packaged products such as sausages and hot dogs had the lowest level of contamination. These findings are consistent with other reports in which the highest amount of microbial contamination was found in chicken and the lowest in sausage, respectively ( Cansian et al, 2005 ; Ibrahim et al, 2014 ; Trimoulinard et al, 2017 ). These results suggest that chicken may be a potential source of Actinomycetes contamination in meat and meat products and highlight the importance of implementing appropriate measures to ensure the safety of meat and meat products for consumers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, our results showed that chicken had the highest level of contamination, while packaged products such as sausages and hot dogs had the lowest level of contamination. These findings are consistent with other reports in which the highest amount of microbial contamination was found in chicken and the lowest in sausage, respectively ( Cansian et al, 2005 ; Ibrahim et al, 2014 ; Trimoulinard et al, 2017 ). These results suggest that chicken may be a potential source of Actinomycetes contamination in meat and meat products and highlight the importance of implementing appropriate measures to ensure the safety of meat and meat products for consumers.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, according to the mentioned statistical formula, the number of sampling locations, and the number of samples in similar studies, 60 meat and meat products samples were collected, of which 21 (35%) actinomycete isolates were isolated. This isolation rate is consistent with other actinomycete isolation reports ( Cansian et al, 2005 ; Ibrahim et al, 2014 ; Trimoulinard et al, 2017 ). However, this result cannot be accurately reported as the prevalence rate due to the limitation and small volume of samples.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that 19 named species have been classified, only few of them are recognized as human pathogens, such as A. hydrophila complex, A. caviae and A. veronii, representing almost 85% of the clinical isolates, although other species have been recovered from the clinical sources (Janda and Abbot, 1998). Aeromonads are also found in a variety of sources, such as the food (Granum et al, 1998;Cansian et al, 2005;Ullmann et al, 2005;Martin Talavea et al, 2006), natural water (Ghenghesh et al, 2001;Østensvik, 2001, Sousa andSilva-Souza 2001) and drinking water (Kuhn et al, 1997;Villari et al, 2003), and it is known that psycrophilic species are mainly etiologic agents in the fishes (Garduño et al, 2000). In human immunocompetent hosts, the members of this genus may be responsible for the intense gastroenteritis, called traveler's diarrhea (Janda and Abbot, 1998;Vila et al, 2003), but in the immunocompromised hosts, these bacteria could be implicated in the cases of myonecrosis, bacteremia, septicaemia (Martino et al, 1997) and hepatic cirrhosis and neoplasys (Chien Ko and Chuang, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Processing a chicken for the human consumption requires 12 to 24L of water (Chaves et al, 2005). According to the Brazilian Union of Aviculture, the production of chicken in 1998 was around 4.5x10 6 ton (Cansian et al, 2005). The variation in quantity and organic load present in the effluents from different industries depends on the degree of recycling and care taken during the operation, particularly with blood (Ruiz et al, 1997;Pohlmann, 2004).…”
Section: Introductionmentioning
confidence: 99%